Variations in pollen and fungal spore air spora: an analysis of 30 years of monitoring for the clinical assessment of patients in the Western Cape - Berman, Dilys Melanie (Department of Medicine, 2019)
Background and aims: Pollen and fungal spore concentrations in the atmosphere of Cape Town have been monitored since 1984 in two areas of Cape Town. Volumetric spore traps were used to monitor the air spora that trigger allergic disease in susceptible individuals. A pollen count was produced for the diagnosis and treatment of patients attending respiratory clinics at the academic hospitals but the findings of the different aerobiological monitoring areas have never been compared. We considered that more than one aerobiological area should be monitored to produce a representative pollen count for the most densely populated areas of Cape Town. Methods: The pollen taxa and fungal spore genera collected from the two aerobiological zones, now named the West Coast and Valkenberg Aerobiomes were defined. Eight of the air spora were selected for detailed comparison. The relative abundance and seasons of Poaceae, or grasses, the tree pollen taxa Cupressaceae, Platanus and Quercus and the fungal spores: Alternaria, Cladosporium, Epicoccum and Pleospora were evaluated and compared in each aerobiome. Differences in the annual distribution and seasonal limits of the air spora in the two aerobiomes were found using statistical techniques. Results: Significant differences were found between the tree pollen loads in the different aerobiomes. Spring pollinating trees were the most prevalent pollen taxa in the Valkenberg Aerobiome with short flowering seasons that spanned six weeks (August-September) for Platanus and Quercus but eight weeks (July-September) for Cupressaceae. The grass season was longer (September- March) in both aerobiomes and grasses flowered earlier at the inland site. Poaceae dominated the annual pollen catch at the coastal aerobiological zone. Parietaria was the only weed taxon with significant concentrations. Pleospora showed a seasonal trend peaking in mid to late winter at the West Coast. No comparable peaks for Pleospora were seen from the Valkenberg sites. Cladosporium concentrations were low and seldom breached the significant threshold of 3,000 spores/m-3 in either of the aerobiomes. The influence of meteorological parameters on Cladosporium and temperature on Poaceae was explored. A table was designed that clarified the ranges for Cladosporium and a formula was adapted for predicting the start of the grass season. Significant decreases in the Poaceae concentrations in both aerobiomes were observed and discussed with reference to Global Warming. Conclusions: The differences in the pollen spectra and seasonality of the selected allergenic air spora indicate that both aerobiomes should be monitored concurrently for patients who live and work in these different microclimates. Pollen profiles for skin, blood and specific IgE testing panels should be reassessed to include Cupressaceae, Parietaria, Myrica, Pleospora and basidiospores. When patients are recruited for clinical drug trials, their place of residence or work should be within the realm of the aerobiome that is being monitored. Current pollen monitoring programmes should be consulted for immunisation regimes to grass and tree pollen. These findings will be applied to the diagnosis and prescription of immunotherapy in clinical practice.